Corporations As Legal Subjects In Environmental Crimes - Agustin Sari, Nur Khalifah; Gunadi , Ariawan (Borong Newinera Publisher, 2024)
This study seeks to examine the legal implications of corporate accountability in relation to environmental crimes. To address this difficulty, we rely on theoretical sources written by Philipus M. Hadjon and Tatiek Sri Djatmiati. They contend that under the civil law system, the first approach should be a legal one. The data were gathered in accordance with the relevant legislation and regulations in Indonesia and were subjected to qualitative analysis. This article asserts that legal liability for criminal actions of environmental harm extends beyond people to include legal organizations or companies as entities subject to criminal law. In this scenario, both the board and the business have equal culpability for committing an environmental offense.